Implementasi Algoritma Sprizt Untuk Mengamankan Database Aplikasi Ujian Semester Berbasis Komputer - Manalu, Magresi (ADA Research Center, 2024)
With the rise of schools conducting computer-based exams, many web-based exam applications have sprung up and can be used free of charge, especially at SMK Alwashliyah Pasar Senen 2 Medan. However, the weakness of the computer-based exam is that there is no security for questions that are stored in the database, of course the questions are confidential data and must be safe. Therefore we need a database security technique to keep the question secret, whether an attack occurs or not. The technique used is cryptographic encryption techniques. This study encrypts the database of computer-based exam questions with the Spritz algorithm. In securing the database of exam questions using cryptographic techniques, the meaning of the questions in the database cannot be understood, so that in the event of an attack, the questions cannot be read and understood by the attacking party, thereby eliminating the level of cheating during the exam. The encryption process is carried out when the admin inputs a question on the admin exam web interface. Meanwhile, the decryption stage is carried out when students carry out a computer-based exam. Based on the manual encryption process on the sample database with the plaintext